Capital structure and firm performance during global financial crisis - Khodavandloo, Marzieh; Zakaria, Zukarnain; Md. Nassir, Annuar (EconJournals, 2017)
The relationship between capital structure and firm performance has been extensively investigated in the recent decades. However, only few studies investigate this relationship during financial crisis. Recent global financial crisis provides an opportunity to examine the effect of the crisis on the relationship between capital structure and firm performance. Therefore, this paper aims to investigate this relationship based on 45 listed companies involved in trading and services sector of the Bursa Malaysia, over three specific periods of recent financial crises; the pre-crisis (2004-2006), crisis (2007-2009), and post-crisis recovery (2010-2013). The study results indicate that financial leverage has a strong negative impact on firms’ performance. These results are stronger during the global financial crisis began in 2007 and ended in 2009. These results observed in both simple regression and cross-sectional analyses even after controlling for firm specific measures.